Antifascism : the course of a crusade - Gottfried, Paul, 1941- (Northern Illinois University Press, an imprint of Cornell University Press, 2021)
"This book deals with the continuing appeal of antifascism as a political concept and as a tool for fighting a real or imagined fascist enemy. Antifascism has undergone significant changes in how it has understood and combatted a perceived fascist danger from the 1920s down to the present"--